Modification of Rubberized Concrete: A Review - Changming Bu; Dongxu Zhu; Xinyu Lu; Lei Liu; Yi Sun; Linwen Yu; Tao Xiao; Wentao Zhang (Buildings, 2022)
One of the environmental problems causing concern in the world today is the black pollution caused by the accumulation of waste rubber resources. Relevant experimental studies have proved that rubber concrete can help solve the black pollution problem caused by waste rubber tires, but it is undeniable that rubber particles will reduce the mechanical properties of concrete. To this end, many studies on the modification of rubberized concrete have been carried out, and this paper summarizes these studies, considering compressive strength, durability performance and insulation performance. The results show that chemical pretreatments, such as sodium hydroxide, can significantly improve the adhesion between rubber particles and cement matrixes. Mineral powder admixtures, such as silica fume and fiber admixtures, e.g., PP fibers, can improve the compressive strength of rubber concrete.